2020
DOI: 10.1111/apm.13025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of CLIA and EIA for Quantiferon‐TB Gold Plus

Abstract: The purpose of this study was to compare the Quantiferon‐TB Gold Plus test analysed with chemiluminescence immunoassay (CLIA) to immunoassay (EIA). One hundred and twenty‐five clinical specimens submitted to Karolinska University Hospital for Quantiferon‐TB Gold Plus analysis were used to analyse agreement of the CLIA and EIA assays. The imprecision on CLIA was determined by analysis of pooled clinical samples of antigen tubes (TB1 and TB2), a reference material from National Institute for Biological Standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…According to this recommendation, agreement between the two assays was moderate (70.4%), lower than the agreement observed when the manufacturer's cutoff was used. Similarly, Brantestig et al found a lower agreement (88%) when using the Swedish National recommendations that define a broad borderline range (0.20 to 0.99 IFN-␥ IU/ml) than when applying the manufacturer's cutoff (96.8%) (12). However, in our study, among the ELISA borderline samples (n ϭ 79), the increased CLIA values remained in the borderline range (0.29 versus 0.59 IU/ml for TB1 and 0.32 versus 0.60 IU/ml for TB2), suggesting that this range may not need to be revised for CLIA.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…According to this recommendation, agreement between the two assays was moderate (70.4%), lower than the agreement observed when the manufacturer's cutoff was used. Similarly, Brantestig et al found a lower agreement (88%) when using the Swedish National recommendations that define a broad borderline range (0.20 to 0.99 IFN-␥ IU/ml) than when applying the manufacturer's cutoff (96.8%) (12). However, in our study, among the ELISA borderline samples (n ϭ 79), the increased CLIA values remained in the borderline range (0.29 versus 0.59 IU/ml for TB1 and 0.32 versus 0.60 IU/ml for TB2), suggesting that this range may not need to be revised for CLIA.…”
Section: Discussionmentioning
confidence: 98%
“…A new fully automated CLIA detection system to measure IFN-␥ in human plasma has recently been developed on the Liaison XL analyzer (DiaSorin, Italy). CLIA repeatability and reproducibility on this platform were studied by Brantestig et al, who found that the imprecision of the method is within an acceptable range and analysis of linearity showed acceptable recovery (12). Furthermore, a recent study by De Maertelaere et al conducted on 92 samples showed that CLIA gave significantly higher values for TB1 and TB2 than ELISA (11).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study reported that the LIOFeron TB/LTBI assay may have higher sensitivity than the QuantiFERON-TB Gold Plus test [28]. Chemiluminescence immunoassays (CLIA) have also been studied in comparison to the QuantiFERON-TB Gold test [29].…”
Section: Newer Igrasmentioning
confidence: 99%
“…A recent study (Della Bella et al, 2020) reported that the LIOFeron TB/LTBI assay may have higher sensitivity than the QuantiFERON-TB Gold Plus test and that further evaluation is required in controlled studies in different geographical areas. Chemiluminescence immunoassays (CLIA) have also been studied in comparison to the QuantiFERON-TB Gold test (Brantestig et al, 2020).…”
Section: Advancing Ltbi Diagnostic Testsmentioning
confidence: 99%